Desire Reflected in Elizabeth Gilbert's The Signature of All Things (2013): A Psychoanalytic Approach - Muna, Nikmah Afiyyatul (2016)
The major problem of this study is desire. Someone who has desire in her life she has to try hard to get it. The objective of this study is to analyze this novel based on the Psychoanalytic Approach. The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source of the study is The Signature of All Things novel by Elizabeth Gilbert. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the novel. The secondary data of the study are taken from any information related to the novel. The method of data collection is the researcher will employ the descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. The study shows that the problem faced by the major character is her desire. It is proven by her ambition to reach her dreams in her life. Alma Whittaker is a naturalist. Alma loves everything about botany. She has many desires in her life. She tries hard to get what she wants. Alma does a lot of efforts and never gives up. Alma realizes without struggle her dreams will not come true.